2017
DOI: 10.5212/rev.conexao.v.13.i1.0015
|View full text |Cite
|
Sign up to set email alerts
|

Educar Para Prevenir: A Importância Da Informação No Cuidado Do Pé Diabético

Abstract: ResumoO artigo é referente a um estudo descritivo, transversal, oriundo do projeto de extensão intitulado "Cuidado e informação: atenção multiprofissional permanente as afecções dermatológicas em pés de pacientes diabéticos", com o objetivo de identificar alterações dermatológicas nos pés e oferecer informações e recomendações ao diabético para prevenção do pé diabético.O estudo foi realizado com 212 pacientes diabéticos atendidos no ambulatório de endocrinologia e clínica médica de um Hospital Universitário, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
0
0
1
Order By: Relevance
“…With compromised skin, the installation of serious infections and amputation of the limb becomes viable, since this is one of the body's protection against external agents. 13 Other studies also corroborate what was found in this study; in this opportunity, with a predominance of skin alterations such as dry skin (90%) and cracks (63%). 14 Among the participants, 62.7% had inadequate nail cutting and 36.3% had unsatisfactory hygiene, the latter not being less important because it is an essential point to avoid future injuries.…”
Section: Discussionsupporting
confidence: 90%
“…With compromised skin, the installation of serious infections and amputation of the limb becomes viable, since this is one of the body's protection against external agents. 13 Other studies also corroborate what was found in this study; in this opportunity, with a predominance of skin alterations such as dry skin (90%) and cracks (63%). 14 Among the participants, 62.7% had inadequate nail cutting and 36.3% had unsatisfactory hygiene, the latter not being less important because it is an essential point to avoid future injuries.…”
Section: Discussionsupporting
confidence: 90%
“…No presente estudo evidenciou-se um número significativo de indivíduos com xerose (pele ressecada) e onicomicose (micose nas unhas). Resultado análogo foi encontrado em estudo (16) realizado em um Hospital Universitário junto a 212 indivíduos com DM que apresentaram algumas afecções nos pés, entre elas a xerose (55,2%) e a onicomicose (43,9%), o que demonstra o quanto o DM prejudica a integridade da pele se não houver os devidos cuidados. Daí a importância dos profissionais de saúde orientar a população quanto às práticas de inspeção dos pés, promovendo ações dinâmicas capazes de transmitir informações de forma acessível e que envolvam a demonstração e supervisão de cuidados específicos.…”
Section: Discussionunclassified